Responses of Multipotent Retinal Stem Cells to IL-1β, IL-18, or IL-17 - Shida Chen; Defen Shen; Nicholas A. Popp; Alexander J. Ogilvy; Jingsheng Tuo; Mones Abu-Asab; Ting Xie; Chi-Chao Chan (Journal of Ophthalmology)
Purpose. To investigate how multipotent retinal stem cells (RSCs) isolated from mice respond to the proinflammatory signaling molecules, IL-1β, IL-18, and IL-17A. Materials and Methods. RSCs were cultured in a specific culture medium and were treated with these cytokines. Cell viability was detected by MTT assay; ultrastructure was evaluated by transmission electron microscopy; expression of IL-17rc and proapoptotic proteins was detected by immunocytochemistry and expression of Il-6 and Il-17a was detected by quantitative RT-PCR. As a comparison, primary mouse retinal pigment epithelium (RPE) cells were also treated with IL-1β, IL-18, or IL-17A and analyzed for the expression of Il-6 and Il-17rc. Results. Treatment with IL-1β, IL-18, or IL-17A decreased RSC viability in a dose-dependent fashion and led to damage in cellular ultrastructure including pyroptotic and/or necroptotic cells. IL-1β and IL-18 could induce proapoptotic protein expression. All treatments induced significantly higher expression of Il-6 and Il-17rc in both cells. However, neither IL-1β nor IL-18 could induce Il-17a expression in RSCs. Conclusions. IL-1β, IL-18, and IL-17A induce retinal cell death via pyroptosis/necroptosis and apoptosis. They also provoke proinflammatory responses in RSCs. Though IL-1β and IL-18 could not induce Il-17a expression in RSCs, they both increase Il-17rc expression, which may mediate the effect of Il-17a.